Leveraging Evidence-Centered Design to Develop Assessments of Computational Thinking Practices. Issue 2 (3rd April 2019) - Snow, Eric; Rutstein, Daisy; Basu, Satabdi; Bienkowski, Marie; Everson, Howard T.
Abstract : Computational thinking is a core skill in computer science that has become a focus of instruction in primary and secondary education worldwide. Since 2010, researchers have leveraged Evidence-Centered Design (ECD) methods to develop measures of students' Computational Thinking (CT) practices. This article describes how ECD was used to develop CT assessments for primary students in Hong Kong and secondary students in the United States. We demonstrate how leveraging ECD yields a principled design for developing assessments of hard-to-assess constructs and, as part of the process, creates reusable artifacts—design patterns and task templates—that inform the design of other, related assessments. Leveraging ECD, as described in this article, represents a principled approach to measuring students' computational thinking practices, and situates the approach in emerging computational thinking curricula and programs to emphasize the links between curricula and assessment design.